Developing Supplementary Speaking Materials For “Bahasa Inggris” Textbook For 1st Grade Pharmacy Students - Nanda Kristia Santoso; Ferri Yonantha; Serly Serly (SALEE: Study of Applied Linguistics and English Education, 2021)
The purpose of this study is to develop supplementary speaking materials for Bahasa Inggris for grade X students of SMK Insan Mulia Yogyakarta and describe the efficacy of the supplementary speaking materials for grade X students of SMK Insan Mulia Yogyakarta. This research belongs to Educational Research and Development (R&D) using a simplified six steps of Borg and Gall’s model (1983). The findings show that the students’ goal of learning English is to communicate with the foreign costumers. Moreover, necessities of students are able to use English in their working field especially pharmacy and it helps students to pass job’s selection besides English is very important because the students are be able to use English in their working field especially pharmacy. more than that, the research finds that the students are lacking of vocabularies and speaking activities in the classroom and The students also lack of English speaking activities in the class because the books only provide reading. More than that, in learning English the students’ wants to learn English with their specific information about pharmacy. Some themes in the textbook were not relevant with the students’ want such as pharmacy, hospital and medicine. The efficacy of the supplementary speaking materials textbook serve the clear instruction and encourage the students in doing activities especially speaking, besides there are various activities in the textbook. This textbook is developed based on the Insan Mulia vocational pharmacy student’s need, lack, and want. Furthermore, the speaking materials as the product of this study provide additional learning resources for students.